SISTEM INFORMASI POSYANDU (SIPOSDU) BERBASIS WEB PADA KELURAHAN KOBER PURWOKERTO - Vembria Rose Handayani Vembria; Paulus Doni Arif Wibowo; Suripah Suripah (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Bina Sarana Informatika, 2022)
Information systems and knowledge about the development of information technology are constantly evolving so that there are many changes in new science at this time. In posyandu activities, of course, a lot of data is recorded and reports are recorded. Especially the data for toddlers every month there must be changes, both in terms of adding and subtracting. This can cause ineffectiveness if the recording is on paper or manually. To facilitate recording, an information system for data collection of children under five at the posyandu is needed. The solution for this problem is develop a web-based posyandu information system. The information system for data collection for children under five at Margi Rahayu was designed using the PHP programming language and MySQL database. Later this information system will help posyandu cadres to process toddler data and report on posyandu activities every month more easily, effectively and efficiently. Keywords : Information System, Web, Posyandu